34BetaE12 and Alfa-Methylacyl Coenzyme A Racemase (AMACR) Antibodies Better Than p63 Antibody Distinguish Normal and Neoplastic Glands in Prostatic Tissue With Thermal Artifacts. Issue 4 (April 2019) - Pierconti, Francesco; Rossi, Esther D.; Martini, Maurizio; Sacco, Emilio; Bassi, Pier F.; Larocca, Luigi M.
Abstract : The occurrence of inked margins with crush artifact derived from the electrocauterization in radical prostatectomy and/or the presence of crushed areas with distorted glands in prostatic samples after transurethral resection of prostate (TURP) can induce a significant interobserver variability during histopathologic evaluation of specimens. The specific immunostaining for basal cell markers 34BetaE12 and p63 and for alfa-methylacyl coenzyme A racemase (AMACR) in neoplastic cells is commonly used as an ancillary tool to establish benign and malignant glands. In this study we carried out the immunohistochemical reactions for p63, 34BetaE12, and AMACR on 3 different and successive paraffin sections to discriminate malignant and benign prostatic glands, distorted and crushed by the thermal artifacts in 60 radical prostatectomies and 50 TURP samples. All prostatic acinar adenocarcinoma showed the loss of basal cell markers and expression of AMACR, whereas p63 failed to stain the basal cell layer in benign crushed prostatic glands. The same cauterized glands were steadily positive for 34BetaE12. The high percentage of p63 false negative cases in benign distorted and crushed glands could be explained by the thermal artifacts which might cause lack of p63 antigenicity. In contrast, the antigenicity of 34BetaE12 and AMACR seem not to be affected by cautery artifacts. Thus, in cauterized suspicious prostatic glands an immunohistochemistry panel including, p63, 34BetaE12, and AMACR or only 34BetaE12 is recommended. In addition, after the first evaluation with only p63, we suggest that a separate and confirmatory staining for 34BetaE12 is strongly recommended.